What makes a hunting experience memorable? - Saayman, Melville, speaker; van der Merwe, Peet, speaker; van Hoven, Wouter, moderator; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
Growth in the number of game farms and hunting lodges (operators) in Southern Africa has created fierce competition amongst these hunting operations. In order to remain competitive it is important to determine what hunters regard as important in order to have a memorable experience. The literature review revealed that different markets (hunters) have different expectations and needs and for that reason the purpose of this paper is to determine the aspects that contribute to a memorable experience of foreign (trophy) hunters who hunted in South Africa in 2013. In addition the paper will also determine which socio demographic and behavioural variables influence memorability. This was achieved by conducting a structured questionnaire survey and the results are of high importance to hunting operators and product developers alike. It is also the first time that such a study is conducted amongst South African international hunters.
Moderator: Wouter van Hoven.
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
Presenter: Petrus van der Merwe
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses